2013
DOI: 10.1158/1535-7163.mct-13-0142
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Thioflavin S–Derived Compound That Inhibits BAG-1–Mediated Protein Interactions and Targets BRAF Inhibitor–Resistant Cell Lines

Abstract: Protein-protein interactions mediated through the C-terminal Bcl-2-associated athanogene (BAG) domain of BAG-1 are critical for cell survival and proliferation. Thioflavin S (NSC71948)-a mixture of compounds resulting from the methylation and sulfonation of primulin base-has been shown to dosedependently inhibit the interaction between BAG-1 and Hsc70 in vitro. In human breast cancer cell lines, with high BAG-1 expression levels, Thioflavin S reduces the binding of BAG-1 to Hsc70, Hsp70, or CRAF and decreases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 60 publications
2
33
2
Order By: Relevance
“…Thioflavin S is a complex mixture of compounds and, originally, its biological activity was not definitively attributed to any one component; however, a subsequent study isolated and purified Thio-2 (Figure 5A), a component which retained the ability of Thioflavin S to block the BAG-1/HSC70 interaction (Enthammer et al., 2013). Despite this advance, the Thioflavin class of molecules, to which Thio-2 belongs, exhibit multiple sources of off-target activities, including CYP1A1-mediated generation of reactive intermediates and DNA-adduct formation (Chakraborty et al., 2010) as well as PAINS motifs (see next section), casting strong doubt upon the credentials of these compounds as high-quality chemical probes.…”
Section: Main Textmentioning
confidence: 99%
“…Thioflavin S is a complex mixture of compounds and, originally, its biological activity was not definitively attributed to any one component; however, a subsequent study isolated and purified Thio-2 (Figure 5A), a component which retained the ability of Thioflavin S to block the BAG-1/HSC70 interaction (Enthammer et al., 2013). Despite this advance, the Thioflavin class of molecules, to which Thio-2 belongs, exhibit multiple sources of off-target activities, including CYP1A1-mediated generation of reactive intermediates and DNA-adduct formation (Chakraborty et al., 2010) as well as PAINS motifs (see next section), casting strong doubt upon the credentials of these compounds as high-quality chemical probes.…”
Section: Main Textmentioning
confidence: 99%
“…We decided to impair BAG-1 function, and test whether it might influence leukemia cells sensitivity to drugs. We used Thioflavin S (NSC71948), which has recently been shown to interfere with the ability of BAG-1 to interact with HSP70 in vitro [36,37]. We treated three AML cell lines, HL60 (BAG-1 expression corresponding to >75 th percentile), ML-2 (<50 th percentile) and THP-1 (>75 th percentile; Table 3 To assess if observed increase in the efficiency of drug action occurred due to synergic activity among combined drugs, we calculated the combination index (CI) according to the Chou and Talalay method [29].…”
Section: Bag-1 Down-regulation Induced Moderate Cell Death and Modulamentioning
confidence: 99%
“…Bcl-2-associated athanogene-1 exists as three main isoforms, which are produced by alternative translation initiation from a single mRNA (Packham et al , 1997). Bcl-2-associated athanogene-1L is found in the nucleus, whereas BAG-1M and BAG-1S are generally found in the cytoplasm (Packham et al , 1997; Takayama et al , 1998; Brimmell et al , 1999; Schneikert et al , 1999; Yang et al , 1999; Knee et al , 2001), and the possibility of BAG-1 directed therapy has been suggested from laboratory studies (Sharp et al , 2009a, 2009b; Enthammer et al , 2013). In the clinical setting, BAG-1 mRNA has been incorporated as a prognostic biomarker in Oncotype DX (Paik et al , 2004) and PAM50 (Parker et al , 2009) multigene assays, which estimate prognosis following surgery, and can be used to assess the potential benefit of chemotherapy for breast cancer.…”
mentioning
confidence: 99%